Fairy Tales And Reading Skills - Núñez Lescano, Romina Betsabé; Mantilla Carrera, Paola Nathaly; León Mejía, Edmundo Francisco; Romero Rodríguez , Lucia Elizabeth; González Paladinez, Mónica Cristina (Arandu UTIC, 2024)
The current research is demanded to cover an examination accomplished with the succeeding topic: “Fairy Tales and Reading Skills” which investigates the relationship among both variables and how students’ understudies improve their reading subskills. Firstly, it is necessary to mention that reading is not considered in the way it should be in education. As a result, it leads to poor use of resources to develop reading skills. Thus, English teachers affirm that the four language skills should be developed in an integrated way because they complement each other. Therefore, the current research aims to recognize the impact of fairy tales on reading skills. Secondly, this research was carried out to scrutinize the importance of fairy tales in reading skills on the 4th level at “Unidad Educativa Bilingue La Granja”. The participants of the study were 17 students; 10 men, and 7 women. The current project had a qualitative approach and descriptive research. Thirdly, a 20 questions survey was applied to identify the use of fairy tales in the development of reading skills and the frequency that different resources are used in English classes. Finally, discerning the results of the survey, the rejection of the null hypothesis was established. Consequently, the acceptance of the alternative hypothesis was verified by corroborating that Fairy Tales influence the improvement of reading skills, and it is advised the implementation of fairy tales as a resource in English teaching methodologies.